Market-pull policies to promote renewable energy: a quantitative assessment of tendering implementation - Bento, N.; Borello, M.; Gianfrate, G. (Journal of Cleaner Production, 2020)
Policymakers ideally select the support mechanism that better foments renewable energy production at the lowest cost to comply with international climate agreements. Currently, tendering is the fastest rising scheme. Yet a quantitative assessment of its performance in the literature is missing. We assess the effect of the introduction of auctions in accelerating the addition of renewable capacity through three econometric models: fixed-effects multivariate regression, statistical matching and synthetic control. The dataset includes 20 developed countries, spanning from 2004 to 2014, and both macroeconomic and policy drivers. Results show that tendering has the strongest effects to promote net renewable capacity comparing to other mechanisms like feed-in tariffs. Countries implementing tendering on average have a higher addition of net capacity of renewables in the order of 1000-2000 MW annually. The positive effect of tenders is clearer when analyzing with synthetic controls the case of Italy: while tendering enhances the deployment of renewables, policy instability jeopardizes the sustainability of tendering’s impact.